LIMPEZA DE GÁS EFICIENTE ENERGÉTICA - Design ótimo do sistema de Exaustão - Herrmann Flor (Associacao Brasileira de Metalurgia, Materiais e Mineracao, 2017)
In steelmaking process, where up to 70% of variable cost of finished product is already incurred, energy and refractory costs account for 45-50% of the cost of production of crude steel and contribute significantly to the carbon footprint of the end product. Any attempt to control and reduce these costs will automatically lead to more competiveness and reduced carbon emissions. Leading the technology for ECOPLANT (characterized by the fact that the economic and ecological benefits are integral part of our products), SMS has developed innovative solutions which can be applied to both new and existing plants alike. This paper reviews one of the electrical and automation concepts. Tackling the secondary gas cleaning system and hence being applicable to almost all steel plants, the X-Pact® Gas Cleaning Assistant optimizes the control of individual dampers based on modelling of fluid resistances of ductwork in gas cleaning system. It guarantees the best dust removal from work place at minimum energy consumption.